KAJIAN SOSIO YURIDIS TERHADAP PERKAWINAN ANAK DI BAWAH UMUR STUDI KASUS PADA KECAMATAN MARAWOLA - Suhri Hanafi; Hamiyuddin Hamiyuddin (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2017)
This study was entitled "The juridical socio-marriage study under the age of Marawola district‛ This study aims to describe the factors that cause the occurrence of marriage of children under the age that occurred in Marawola district. The results of this study indicate that substantively the occurrence of young marriage in adolescents in some villages in the district marawola district is a complex problem that can not be separated from social problems, economic, religious culture. This means that the occurrence of young marriage associated with various factors such problems. parents' concerns about the current patterns of intercourse encourage parents to immediately marry off their children. This research becomes an ingredient for parents, so as not to rush to marry off minors (adolescents). Because adolescents have not been able to deal with and solve the problems of the household well. The teenagers still need a lot of good stock of physical maturity, mental and social economy, general science, religion, life experiences in married life. The study was conducted in Marawola District of Sigi Regency.